EVALUASI IMPLEMENTASI KEPUTUSAN WALIKOTA PEKANBARU NOMOR 07 TAHUN 2004 TENTANG PETUNJUK PELAKSANAAN PENGELOLAAN KEBERSIHAN (Studi di Kecamatan Bukit Raya Kota Pekanbaru Pada Tahun 2012) - Vera Siska; Hery Suryadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study seeks to analyze the implementation of the evaluation form ofPekanbaru Mayor Decree No. 07, 2004 on Implementation Guidelines forManagement of Health by the Department of Health and by the District of Bukit Rayagovernment as the authority delegated by the Mayor. Furthermore, in terms of hygienemanagement in Pekanbaru city, especially in Bukit Raya district found indications areless than the maximum hygiene management by sub-district. The lack of infrastructure,limited the ability of the District to provide good public services in waste managementand the lack of effort made to move the sub-district community worked together tocreate awareness of waste management in the district has not done well. As a referenceanalysis, the literature review of the concept of leadership, delegation of authority,policy, policy evaluation and evaluation of the implementation of policies referencedin the study analysis. Furthermore, the study was conducted with descriptive surveyapproach was conducted in Bukit Raya, Pekanbaru City.The results of this study indicate that the implementation of Mayor Decree No.07, 2004 on Implementation Guidelines for Management of Health in particular theimplementation of tasks in the district of Bukit Raya sub-district government, overallcategorized quite done, because the sub-district government had socialized MayorDecree No. 07, 2004, in coordination with relevant agencies or institutions andoversee the implementation of hygiene management, but moving the mutual aid plancleanliness and hygiene infrastructure is not running optimally. Barriers toimplementation of the Mayor's Decision No. 07 Year 2004 on ImplementationGuidelines for Management of Health in Bukit Raya district , among others, thecomplexity of tasks and responsibilities carried by government; hygiene facilities andinfrastructure available and the quantity janitor is not proportional to the population ofgarbage; most people's lack of understanding of the importance of environmentalhygiene management; and the lack of legal sanctions against violations of regulationsimposed.Keywords: Policy, Evaluation and Authority